Studies directed towards the synthesis of chromone carbaldehyde-derived HIV-1 protease inhibitors - Molefe, Duduzile Mabel (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
A series of chromone-3-carbaldehydes have been prepared using Vilsmeier-Haack methodology while a corresponding series of chromone-2-carbaldeydes have been synthesized via the Kostanecki-Robinson reaction. Baylis-Hillman reactions have been conducted on both series of chromone carbaldehydes using three different catalysts, viz., 1,4-diazabicyclo(2.2.2]octane (DABCO), 1,8-diazabicyclo[5.4.0]undec- 7-ene (DBU) and 3-hydroxyquinuclidine (3HQ), and acrylonitrile, methyl acrylate and methyl vinyl ketone as the activated alkenes. These reactions have typically (but not always!) afforded both normal Baylis-Hillman and dimeric products. Attention has also been given to the use of 1-methyl-2-pyrrolidine (1-NMP), an ionic liquid, to replace normal organic solvents, and it has been found that, in the presence of DABCO, chromone-3-carbaldehydes afford the dimeric products alone. Reactions of chromone-3-carbaldehydes with methyl vinyl ketone have yielded unexpected, novel adducts, which appear to arise from preferential attack at C(2) in the chromone nucleus. Research on chromone-2-carbaldeydes under Baylis-Hillman conditions has also resulted in the formation of some interesting products instead of the expected Baylis-Hillman adducts. The Baylis-Hillman products have been explored as substrates for aza-Michael reactions using various amino derivatives including protected amino acids in the presence of the tetrabutylammonium bromide (TBAB) and the ionic liquid, 3-butyl-1- methylimidazoleboranetetrafluoride (BmimBFâ‚„), as catalysts. The aza-Michael products have been targeted as truncated ritonavir analogues for investigation as potential HIV -1 protease inhibitors, and representative compounds have been subjected to enzyme inhibition assays to explore the extent and type of inhibition. Lineweaver-Burk and Dixon plots have indicated competitive inhibition in one case as well as non-competitive inhibition in another, and the inhibition constants (Ki) have been compared with that of the ritonavir. Computer modelling studies have also been conducted on selected chromonecontaining derivatives, using the ACCELRYS CeriusÂ² platform. Interactive docking of the chromone-containing ligands into the HIV -1 protease receptor site, using the Ligandfit module, has indicated the importance of hydrogen-bonding interactions mediated by bridging water molecules situated in the receptor cavity. NMR spectroscopy has been used to elucidate complex and competing mechanistic pathways involved in the Baylis-Hillman reactions of selected 2-nitrobenzaldehydes with MVK in the presence of DABCO - reactions which afford the normal BaylisHillman product, the MVK dimer and syn- and anti-Baylis-Hillman type diadducts. The kinetic data confirm the concomitant operation of two pathways and reveal that, in the initial stage of the reaction, the product distribution is kinetically controlled, whereas in the latter stage, thermodynamic control results in the consumption of the normal Baylis-Hillman product and predominance of the anti-diadduct.
Keywords: Protease Inhibitors; HIV infections; HIV (Viruses); AIDS (Disease); Proteolytic enzymes; Heterocyclic compounds -- Derivatives; Chemical kinetics; Nuclear magnetic resonance spectroscopy